2020
DOI: 10.3390/app10176065
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization and Modification of Bitumen by Silica Nanoparticles

Abstract: A study on the effect of silica nanoparticles (SNPs) dispersion in bitumen is herein reported. First, the size of the nanoparticles was finely tuned by controlling the experimental conditions during their synthesis, obtaining spherical SNPs with diameter ranging from 95 up to 900 nm. Subsequently, SNPs were embedded with peripheral amine groups by using APTES (3-aminopropyltriethoxysilane) as functionalized agent (NH2@SNP), and ultimately long alkyl chains were grafted by reacting the free amine with an alkyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As expected, FM in our study was the highest for QuiXfil and decreased towards materials with lower filler contents, namely SDR and Tetric PowerFlow. Masouras et al [ 31 ] pointed out that the amount of filler is the most important factor for FM, while the shape and size of the filler play a minor role [ 32 , 33 , 34 ]. In addition to the filler content, Randolph et al [ 35 ] found that materials with pre-polymerised particles had lower FM values compared to the other materials tested.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, FM in our study was the highest for QuiXfil and decreased towards materials with lower filler contents, namely SDR and Tetric PowerFlow. Masouras et al [ 31 ] pointed out that the amount of filler is the most important factor for FM, while the shape and size of the filler play a minor role [ 32 , 33 , 34 ]. In addition to the filler content, Randolph et al [ 35 ] found that materials with pre-polymerised particles had lower FM values compared to the other materials tested.…”
Section: Discussionmentioning
confidence: 99%
“…Special increased requirements are placed on bitumen in the construction of highways of higher technical categories and in conditions of harsh continental climates. To improve the physical and mechanical characteristics of bitumen, they are currently being modified with the addition of various fillers [ 1 ].…”
Section: Introductionmentioning
confidence: 99%